Continuous Infusion Nonsteroidal Anti-Inflammatory Drugs for Perioperative Pain Management. (February 2018) - Howard, Meredith L.; Isaacs, Alex N.; Nisly, Sarah A.
Purpose: To review the use of continuous infusion (CI) nonsteroidal anti-inflammatory drugs (NSAIDs) as an alternative modality for pain control in surgical patient populations. Methods: A PubMed and MEDLINE search was conducted from 1964 through February 2016 using the following search terms alone or in combinations: continuous, infusion, nonsteroidal anti-inflammatory drug, diclofenac, ibuprofen, indomethacin, ketoprofen, ketorolac, and surgery. All English-language, prospective and retrospective, adult and pediatric studies evaluating intravenous or intramuscular CI NSAIDs for surgical pain were evaluated for inclusion in this review. Results: Twenty four prospective and retrospective publications evaluating CI NSAIDs were identified: 12 in abdominal surgery, 7 in orthopedic surgery, and 5 in pediatric surgery. Specific CI NSAIDs utilized included diclofenac, indomethacin, ketoprofen, and ketorolac. Most studies compared the CI NSAID to placebo or an alternative analgesic and evaluated pain control, supplemental opioid use, and related adverse effects. In these surgical populations, CI NSAIDs decreased opioid consumption, alongside provision of adequate pain control. While long-term adverse effects were rarely collected, a decrease in nausea and sedation was often seen with the CI NSAID groups. Conclusions: In the abdominal, orthopedic, and pediatric surgical populations, CI NSAIDs represent a feasible alternative modality for perioperative pain control.